2013
DOI: 10.1017/s1751731112002431
|View full text |Cite
|
Sign up to set email alerts
|

The influence of a magnesium-rich marine extract on behaviour, salivary cortisol levels and skin lesions in growing pigs

Abstract: Growing pigs can display undesirable behaviours, reflecting or causing poor welfare. Addition of magnesium (Mg) to the diet could reduce these, as Mg supplementation has been associated with improved coping ability in response to stress. This study examined the effect of supplementation with a Mg-rich marine extract-based product (Supplement) on the behaviour, skin and tail lesion scores and salivary cortisol concentrations of growing pigs. At weaning (28 days), 448 piglets were assigned to either Control or S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 45 publications
2
31
0
Order By: Relevance
“…Previous studies have shown that skin lesion scores were related to the aggressive behavior in pigs (O'Driscoll et al, ). Aggressive behavior reduced gradually after the teat order had been established (Skok & Skorjanc, ).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies have shown that skin lesion scores were related to the aggressive behavior in pigs (O'Driscoll et al, ). Aggressive behavior reduced gradually after the teat order had been established (Skok & Skorjanc, ).…”
Section: Discussionmentioning
confidence: 96%
“…Welfare of pigs can be assessed by physiological and behavioral indicators, such as heart rate (von Borell et al, ), body temperature (Soerensen & Pedersen, ), serum immunoglobulin and cytokine (Torrey et al, ), lesions on the body and tail of pigs (O'Driscoll, O'Gorman, Taylor, & Boyle, ; Teixeira & Boyle, ), lesions on the teats of sows (Gallois, Cozler, & Prunier, ), and positive and negative social behaviors (Welfare Quality, ).…”
Section: Introductionmentioning
confidence: 99%
“…Further experiments with more dogs must take place; however, the variation of serum Mg 2+ levels of dogs may become one of biomarkers that reflect physical status of dogs. Previous research has shown that pigs became healthier after administration of the Mg 2+ supplement (O'Driscoll et al, 2013). Supplementation of Mg 2+ in healthy dogs with vigorous exercise or training regimes must be discussed for animal welfare.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, subchronic supplementation with Mg in elderly subjects reduced cortisol concentration without a change in ACTH level (21). Furthermore, in the study on pigs where a Mg-rich marine extract-based supplement was added for four weeks, O'Driscoll et al (22) showed that supplemented pigs had significantly lower salivary cortisol accompanied with reduction in aggressive behavior. On the contrary, Cinar et al (23) showed an increase in ACTH after one-month-long supplementation with magnesium.…”
Section: Discussionmentioning
confidence: 99%